The **a ^{2} - b^{2} formula** is also known as "the difference of squares formula". The a square minus b square is used to find the difference between the two squares without actually calculating the squares.

- It is one of the algebraic identities.
- It is used to factorize the binomials of squares.

## What is a^2-b^2 Formula?

The a^{2} - b^{2} formula is given as: **a ^{2} - b^{2} = (a - b) (a + b)**.

If you would like to verify this, you can just multiply (a - b) and (a + b) and see whether you get a^{2} - b^{2}.

### Verification of a^{2} - b^{2} Formula

Let us see the proof of a square minus b square formula. To verify that a^{2} - b^{2} = (a - b) (a + b) we need to prove LHS = RHS. Let us try to solve the equation:

a^{2} - b^{2} = (a - b) (a + b)

Multiply the binomials (a - b) and (a + b) we get

(a - b) (a + b)

=a (a + b) - b (a + b)

=a^{2} + ab - ba - b^{2}

=a^{2} + 0 + b^{2}

=a^{2} - b^{2}

Hence Verified

a^{2} - b^{2} = (a - b) (a + b)

You can understand the a^{2} - b^{2} formula geometrically using the following figure:

☛ **Also Check:**

- (a-b)^2 Formula
- (a+b)^2 Formula

## Proof of a^2 - b^2 Formula

The proof that the value a^{2} - b^{2} is (a + b)(a - b). Let us consider the above figure. Take the two squares of sides a units and b units respectively. They can be arranged such that two rectangles are also formed as shown in the above figure.

One rectangle has a length of 'a' unit and a breadth of (a - b) units on the other side the second rectangle has a length of (a - b) and a breadth of 'b' units. Now add the areas of the two rectangles to obtain the resultant values. The respective areas of the two rectangles are (a - b) × a = a(a - b) , and (a - b) × b = b(a - b). The sum of the areas of rectangles is the actual obtained resultant expression i.e., a(a - b) + b(a - b) = (a - b)(a + b). Again re-arranging the individual rectangles and squares, we get: (a + b)(a − b) = a^{2} − b^{2}.

Cuemath is one of the world's leading math learning platforms that offers LIVE 1-to-1 online math classes for grades K-12. Our mission is to transform the way children learn math, to help them excel in school and competitive exams. Our expert tutors conduct 2 or more live classes per week, at a pace that matches the child's learning needs.

Want to find complex math solutions within seconds?

Use our free online calculator to solve challenging questions. With Cuemath, find solutions in simple and easy steps.

Book a Free Trial Class

## Examples on a^2-b^2 Formula

Let us solve some interesting problems using the a^2-b^2 formula.

**Example 1:** Using a^{2} - b^{2} formula find the value of 106^{2} - 6^{2}.

**Solution:** To find: 100^{2} - 6^{2}.

Let us assume that a = 100 and b = 6.

We will substitute these in the a^{2} - b^{2} formula.

a^{2} - b^{2} = (a - b) (a + b)

106^{2}- 6^{2} = (106 - 6) (106 + 6)

= (100) (112)

= 11200

**Answer:** 106^{2} - 6^{2} = 11200.

**Example 2:** Factorize the expression 25x^{2} - 64.

**Solution:** To factorize: 25x^{2} - 64.

We will use the a^{2} - b^{2} formula to factorize this.

We can write the given expression as

25x^{2} - 64 = (5x)^{2} - 8^{2}

We will substitute a = 5x and b = 8 in the formula of a^{2} - b^{2}.

a^{2} - b^{2} = (a - b) (a + b)

(5x)^{2} - 8^{2} = (5x - 8) (5x + 8)

**Answer:** 25x^{2} - 64 = (5x - 8) (5x + 8)

**Example 3:** Simplify 10^{2} - 5^{2} using a^{2} - b^{2} formula

**Solution:** To find 10^{2} - 5^{2}

Let us assume a = 10 and b = 5

Using formula a^{2} - b^{2} = (a - b) (a + b)

10^{2} - 5^{2} = (10 - 5) (10 + 5)

= 10(10 +5) - 5(10 + 5)

= 10(15) - 5(15)

= 150-75 = 75

**Answer:** 10^{2} - 5^{2} = 75.

## FAQs on a^2 - b^2 Formula

### What is the Expansion of a^{2} - b^{2} Formula?

**a ^{2} - b^{2} formula** is read as a square minus b square. Its expansion is expressed as a

^{2}- b

^{2}= (a - b) (a + b).

### What is the a^{2} - b^{2} Formula in Algebra?

The a^{2} - b^{2} formula is also known as one of the important algebraic identities. It is read as a square - b square. a^{2} - b^{2} formula is expressed as a^{2} - b^{2} = (a - b) (a + b). It says, the difference of squares of two numbers is the product of their sum and the difference.

### What is the Difference Between a square - b square and a - b Whole Square?

These two formulas are completely different:

- a
^{2}- b^{2}= (a - b) (a + b) - (a - b)2 = a
^{2}+ b^{2}- 2ab

### How to Simplify Numbers Using the a^{2} - b^{2} Formula?

Let us understand the use of the a^{2} - b^{2} formula with the help of the following example.

**Example:** Find the value of 10^{2} - 2^{2} using the a^{2} - b^{2} formula.

To find: 10^{2} - 2^{2}

Let us assume that a = 10 and b = 2.

We will substitute these in the formula of a^{2} - b^{2}.

a^{2} - b^{2} = (a - b) (a + b)

10^{2}-2^{2} = (10 - 2)(10 + 2)

= 10 (10 + 2) - 2 (10 + 2)

= 10(12) - 2(12)

=120 - 24 = 96

**Answer:** 10^{2} - 2^{2} = 96.

### How To Use the a^{2} - b^{2} Formula Give Steps?

The following steps are followed while using a square - b square formula.

- First, observe the pattern of the numbers and whether the numbers have ^2 as power or not.
- Write down the formula of a
^{2}- b^{2} - a
^{2}- b^{2}= (a - b) (a + b) - Substitute the values of a and b in the a
^{2}- b^{2}formula and simplify.

### Is a Square Minus b Square Same as a Square Plus b Square?

No, these two have different formulas:

- a
^{2}- b^{2}= (a - b) (a + b) - a2 + b2 = (a + b)
^{2}- 2ab